Professional Disease Management Guide for Ornamental Plants - S. D. Bledsoe; Phil F. Harmon; Robert J. McGovern (EDIS, 2004)
This publication is intended to be used by growers, landscape professionals, and other pest control operators as a reference for managing diseases of ornamental plants. Management tactics are outlined under the following key components of an IPM program: prevention, cultural control, scouting, physical control, biological control, and chemical control. Tables 1 - 4 contain important information on commercial products currently available for the management of diseases in ornamental plants. In addition, a list of useful websites and references is provided at the end of this document to supplement the information provided herein. This document is PP202, one of a series of the Plant Pathology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date October 2004.